Design, synthesis and anti-bacterial evaluation of novel 1, 3, 4-thiadiazole derivatives bearing a semicarbazone moiety. (3rd July 2018) - Wan, Jinlin; Gan, Yiyuan; Hu, Weinan; Meng, Jiao; Tian, Kun; Li, Xiaoqin; Wu, Shouqun; Xu, Yang; Ouyang, Guiping; Wang, Zhenchao
GRAPHICAL ABSTRACT: ABSTRACT: Novel 1, 3, 4-thiadiazole derivatives bearing a semicarbazone moiety were prepared and evaluated for their anti-bacterial activities against Xanthomonas oryzae pv. oryzae (Xoo ) and Xanthomonas axonopodis pv. citri (Xac ) by performing a turbidimetre test. The products were structurally characterised by IR, 1 H NMR, 13 C NMR, 19 F NMR and HRMS. Anti-bacterial testing showed that most of the evaluated compounds (6a-6s ) exhibited excellent activity (≥74.19%) against Xoo at a concentration of 200 µg/mL, with 50% effective concentration (EC50 ) values ranging from 12.21 to 67.20 µg/mL, which were superior to the commercial antibacterial agent bismerthiazol (92.23 µg/mL). Among them, compound 2-((2-chloro-1H-indol-3-yl)methylene)-N-(5-((2-chlorobenzyl)thio)-1, 3, 4-thiadiazol-2-yl)hydrazine-1-carboxamide (6b ) demonstrated good inhibitory activity against Xac (89.46% at 200 µg/mL) and Xoo (EC50 = 18.28 µg/mL); compound 2-((2-chloro-1H-indol-3-yl)methylene)-N-(5-((4-methoxybenzyl)thio)-1, 3, 4-thiadiazol-2-yl)hydrazine-1-carboxamide (6g ) displayed excellent activity against Xoo with EC50 value of 12.21 µg/mL.